Harry Potter and the Chamber of Secrets : Vol.2 - Rowling, J. K. (London Bloomsbury, 2014)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school
Include Illustration
Keywords: Potter, Harry -- (Fictitious character) -- Fiction -- Potter, Harry -- (Fictitious character) -- Potter, Harry (Fictitious character) -- Juvenile fiction